(untitled) - Oima, Yoshitoki; LeCroy, Steven; Mizuno, Hiroko (New York, 2016)
"Time stands still for both Shoya and Shoko. Triggered by past traumas, Shoya coldly attacked his friends and burnt the bridges he first set out to rebuild. Shoko feels a deep responsibility for this disaster and attempts to pay for it by taking her own life. Meanwhile, each of their friends finally show their true colors. After everything has fallen apart, how will they mend their hearts and put the pieces back together?"--Provided by publisher.
Keywords: Ficton; Bullying; Fiction; Bullies; Fiction; Conduct of life; Fiction; School children; Fiction; Teenagers; Deaf children; Fiction; Translations into English; Japan; Comic books, strips, etc; Deaf children; Bullying; Comic books, strips, etc; Bullies; Comic books, strips, etc; Comic books, strips, etc; Comic books, strips, etc; School children; Comic books, strips, etc; Teenagers; Comic books, strips, etc; Conduct of life; Manga; Comics (Graphic works)